External mass transfer model for the hydrolysis of palm olein using immobilized lipase - 357330 Chew, Yin Hoon; Lee, Chew Tin (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Sarjana Kejuruteraan (Bioproses)) - Universiti Teknologi Malaysia, 2007